Anosognosia and Memory Encoding in Huntington Disease. Issue 1 (March 2022) - Considine, Ciaran Michael; Hughes, Shelby; Sellers Gibson, Jessie; Isaacs, David; McDonell, Katherine; Darby, R. Ryan; Claassen, Daniel
Abstract : Background: Anosognosia can manifest as an unawareness of neurobehavioral symptoms in individuals with Huntington disease (HD). Measurement of anosognosia is challenging, but the Anosognosia Scale (AS) represents a brief option with promising findings in small samples. Objective: To replicate application of the AS in a larger HD sample than previous studies in order to assess psychometrics and demographic correlates and to investigate the genetic, motor, and neuropsychological correlates of the AS in individuals with HD. Method: We retrospectively reviewed the AS ratings of 74 genetically confirmed Huntington gene carriers, nearly all early motor manifest, who had been referred for clinical neuropsychological assessment. Concurrent clinical neurologic examination and neuropsychometric assessment data were compiled, where available (ns = 35–74). The severity of the anosognosia per AS ratings was characterized for the HD sample. Results: The AS ratings did not correlate with demographic variables, genetic markers, or motor dysfunction severity. Correlation analyses revealed that higher AS ratings correlated with worse recognition–discrimination memory performance ( r = 0.38, P < 0.05) but not cognitive control on executive functioning performance or on collateral-reported frontal–behavioral symptoms. Higher AS ratings also correlated with fewer patient-reported depressive symptoms ( r = –0.38, P < 0.01) and diurnal hypersomnia symptoms ( r = –0.44, P < 0.01). Conclusion: Anosognosia (per AS) is associated with recognition–discrimination deficits and fewer self-reported neuropsychiatric symptoms in individuals with pre-to-early manifest HD, though not with HD severity per genetic or motor markers, nor to executive dysfunction or collateral-reported frontal–behavioral symptoms.